Joaquín Murat y el levantamiento del 2 de mayo: la perspectiva española y la francesa a través de sus testimonios - Paolo, Marilicia di; Varchetta, Jacopo (Acta Hispanica, 2017)
The article aims to present two perspectives, the Spanish and the French one, on the uprising of May 2nd and the previous French occupation of the city of Madrid. In order to delineate the French perspective, letters written by Murat himself to Napoleon will be analyzed; on the other hand, in order to analyze the opinion of the Spanish population, emphasis will be placed on distant expressive forms, such as painting, some examples will be given by Los fusilamientos by Goya, literature with Benito Pérez Galdós’ National Episods, Letters from Spain by Blanco White, Alejo Carpentier’ s Explosion in a Cathedral, the most recent film Blood of May 2008 under the direction of José Luis García Muñoz and more examples of the artistic expression.